Appraisal of knowledge of ASHA regarding child health services provided under NHM in Bhojipura block, District Bareilly - Saxena, Sumit; Singh, Atul Kumar; Maheshwari, Sonam; Gupta, S. B. (International Journal Of Community Medicine And Public Health, 2017)
Background: One of the key strategies under the National Rural Health Mission is having a community health worker who is an Accredited Social Health Activist (ASHA) for every village with a population of 1000. These ASHA workers should preferably be female, in the 25-45 years age group and have a qualification of at least eighth class. The knowledge about health services of ASHA is crucial for the success of National Health Mission. Methods: A cross sectional study was planned in Bhojipura village. Total 48 villages ASHAs were interviewed using predesigned semi-structured questionnaire including brief socio-demographic information of ASHA along with details of their knowledge regarding child care. Results: Out of 64 ASHA, 25 (39.15) ASHA told that new-born babies given bath immediately after birth. 40 (62.5%) ASHA replied that nothing should be applied on umbilical stump of new-born. Mostly 62 (96.9%) ASHA knew that breastfeeding should be given first to the new-born and 61 (95.3%) ASHA were known that breastfeeding should be initiated within one hour of delivery. Conclusions: Majority of ASHAs know their role and details of their practices in new-born and child care except bathing of new born and additional supplements.